Mixed halide perovskites for spectrally stable and high-efficiency blue light-emitting diodes - Max Karlsson (Nature Portfolio, 2021)
Achieving bright and efficient blue emission in metal halide perovskite light-emitting diodes has proven to be challenging. Here, the authors demonstrate high EQE and spectrally stable blue light-emitting diodes based on mixed halide perovskites, with emission from 490 to 451 nm by using a vapour-assisted crystallization technique.